Relationship Between Transformation in Bacillus subtilis and Infection by Bacteriophage SP02 - Stewart, Charles R. (1973)
When bacteriophage SP02 infects a Bacillus subtilis culture during or shortly after transformation, the frequency of transformants among the resulting lysogens is greatly reduced relative to that in the uninfected culture. The effect can occur after the deoxyribonucleic acid has been taken up and covalently attached to recipient deoxyribonucleic acid.